2018
DOI: 10.29252/archhygsci.7.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Fatigue and the Effective Factors in the Iranian Nurses

Abstract: Background & Aims of the Study: Nursing is one of the highly stressful jobs. Nurses have to provide health service, in many cases, to the patients with incurable disease. Working in such environment induces severe and permanent mental pressures, which in long-run can create fatigue and negative effects on performance of the nurses. The main objective of the present study is to survey effects of occupational fatigue and the pertinent factors on the nurses working in Kermanshah hospitals. Materials & Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…In this context, it is important to devise appropriate rest time during work hours and also focus on the needs of the students. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to devise appropriate rest time during work hours and also focus on the needs of the students. 27…”
Section: Discussionmentioning
confidence: 99%
“…When individuals feel fatigued and are not satisfied with their work; they will in general have an awful temper and feel nervousness, anxiety, and disinterest. 27 Fatigue can influence sleep quality as do nightmares, reducing sleep and decreasing academic performance. 28 Chronic fatigue can cause severe fatigue at work, less motivation, more distraction, and poor data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Ziaei et al observed no relationship between sex and visual fatigue (14). If other form of fatigue is effect on this object, we suggest used of other questioner for evaluating (24).…”
Section: Discussionmentioning
confidence: 99%
“…The SOFI questionnaire was studied in several studies on different occupations and was identified as a reliable tool. [ 7 8 9 10 11 12 13 14 15 16 17 18 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…These feelings lead to a conscious effort to maintain or regain attention. [ 8 ] Occupational fatigue has been identified as a risk factor for musculoskeletal disorders. [ 9 10 ] Fatigue can reduce the ability to process hazardous information and respond to relevant conditions.…”
Section: Introductionmentioning
confidence: 99%